2015
DOI: 10.1016/j.bjhh.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin gene polymorphisms and interleukin-6 and -8 levels in patients with sickle cell anemia

Abstract: BackgroundHaptoglobin genotypes, and interleukin-6 and -8 participate in the pathophysiology of sickle cell anemia. The expression of cytokines is regulated by genetic mechanisms however the effect of haptoglobin polymorphisms on these cytokines is not fully understood. This study aimed to compare the frequency of haptoglobin genotypes and the interleukin-6 and -8 concentrations in sickle cell anemia patients and controls to investigate the association between haptoglobin genotypes and cytokine levels.MethodsS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 32 publications
2
17
2
Order By: Relevance
“…The results reported by Pierrot-Gallo et al 15 do not support a conclusion that the Hp genotypes can modulate the inflammatory response in the patients they studied. Nevertheless, the possibility that Hp polymorphisms may contribute to the clinical diversity observed in this condition, in combination with other genetic and environmental factors, should not be excluded.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…The results reported by Pierrot-Gallo et al 15 do not support a conclusion that the Hp genotypes can modulate the inflammatory response in the patients they studied. Nevertheless, the possibility that Hp polymorphisms may contribute to the clinical diversity observed in this condition, in combination with other genetic and environmental factors, should not be excluded.…”
mentioning
confidence: 59%
“…In this volume of the Revista Brasileira de Hematologia e Hemoterapia , Pierrot-Gallo et al 15 analyze the possible influence of Hp genotypes on the secretion of IL-6 and IL-8 in 60 patients with stable SCA (aged 15–50 years old, 53% males; recruited in the Hereditary Anemia Outpatient Clinic of the Hematology and Blood Transfusion Unit, Universidade Federal de São Paulo – UNIFESP, Brazil). A group of 74 apparently healthy individuals (aged 17–60 years old, 53% males; from the same Brazilian region) was used as a control.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, these are different from those of Olatunya et al [ 38 ] in Nigeria, Khalid and Khalil [ 39 ] in Sudan, Moreira and Naoum [ 24 ] in Brazil, and Ostrowski et al [ 23 ] in USA, where the most frequent Hp genotype in SS patients was Hp1-1 (43%, 68%, 36%, and 72%, respectively). Furthermore, the previous work of Bruna et al [ 40 ] in Brazil showed Hp2-1 as the most frequent Hp genotype in SS patients (57%). This multiplicity and the variability of results highlight the need for more studies among many cohorts with diverse ethnic backgrounds to provide more understanding on the Hp polymorphism distribution in SS patients.…”
Section: Discussionmentioning
confidence: 85%
“…The genesis of most clinical manifestations of MS can be increased in patients with HbS, which is especially linked to interrelated mechanisms, such as erythrocyte adhesion, granulocytes, monocytes and platelets to the endothelium. In addition, chronic inflammatory phenomena and cytokine production may also be correlated [ 8 , 9 , 10 ]. Furthermore, adipose tissue also has the secretory ability of various bioactive molecules including adiponectin which is a hormone that has antiatherogenic and anti-inflammatory activity and can be considered as an important biomarker [ 11 ].…”
Section: Introductionmentioning
confidence: 99%